Conceptual Model for SME Digital Transformation during The Covid-19 Pandemic Time in Indonesia: R-Digital Transformation Model - Arianto Muditomo; Indra Wahyudi (Universitas Muhammadiyah Jakarta, 2020)
Digital transformation is one that has been accelerated in response to the COVID-19 pandemic that has hit the world since the end of 2019. As a sector that has proven reliable in facing the SME crisis, it is encouraged to accelerate its digital transformation process due to the distance limitation policy imposed during the pandemic. This article aims to assess the importance of understanding the right digital transformation model for each SME, especially in taking advantage of the accelerated momentum due to the social restriction policies imposed during the COVID-19 pandemic, because choosing the right model will provide a better probability of successful transformation. This research is qualitative research through content analysis to produce a theoretical model construction of the digital transformation model for SMEs in Indonesia which we call the reasonable digital transformation model for SME (R-DT for SME). The conclusion obtained is that based on the mapping of the digital transformation of SMEs in Indonesia on the R-DT model, it can be concluded that: (1) The main trigger for DT UKM is the external driver, not many internal drivers have been found, especially during the COVID-19 pandemic. what is done is still reactive in nature and tends to only follow the steps of the transformation of other actors so as not to create a uniqueness of the said SMEs which will result in the loss of opportunities to have a competitive advantage over competitors; (2) In general, the implementers of DT UKM have set a strategic imperative for their decision to carry out digital transformation, but have not set a measurable milestones so that the digital transformation carried out cannot be measured the level of success; (3) DT which is done in general is to change some of the company's operations to digital, this shows the low digital maturity of SMEs in Indonesia today.